2015
DOI: 10.1111/jam.12728
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of broad-spectrum antipathogen activity of novel rhizobacterial isolates and suppression of Fusarium crown and root rot disease of tomato

Abstract: Indigenous antagonistic bacterial isolates have the potential to be developed as biofungicides for minimizing early crop losses due to soilborne diseases caused by Fusarium and other soilborne pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…The split plate method, when the cultures were grown in liquid instead of solidified medium, led to a reduction in dry fungal biomass in comparison to the control plates. Zhang et al (2014) noted that BVCs were less effective overall than actual bacteria in inhibiting the growth of certain fungi including F. oxysporum . Our results suggested that contact was necessary for complete FOM- and FS-growth inhibition leading us to test whether CF extracts were involved in mycelial growth inhibition, which they were.…”
Section: Discussionmentioning
confidence: 99%
“…The split plate method, when the cultures were grown in liquid instead of solidified medium, led to a reduction in dry fungal biomass in comparison to the control plates. Zhang et al (2014) noted that BVCs were less effective overall than actual bacteria in inhibiting the growth of certain fungi including F. oxysporum . Our results suggested that contact was necessary for complete FOM- and FS-growth inhibition leading us to test whether CF extracts were involved in mycelial growth inhibition, which they were.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggest that fluorescent pseudomonads can have an antagonistic effect that is not necessarily associated with the antibiotics that were searched for here. Several reports on plant-associated pseudomonads indicated also a role of siderophores, lytic enzymes, hydrogen cyanide and ammonia as well as organic volatiles in the inhibition of fungal phytopathogens ( Alimi et al, 2012 ; Loper et al, 2012 ; Müller et al, 2013 ; Zhang et al, 2014 ; De Vrieze et al, 2015 ; Yasmin et al, 2016 ). Wagner et al (2018) most recently examined Pseudomonas strains to identify the gene clusters that are responsible for antagonism against oomycetes by transposon mutagenesis combined with high throughput sequencing and antagonism tests.…”
Section: Discussionmentioning
confidence: 99%
“…GC/MS analysis of headspace extracts from this bacterium revealed the release of 21 compounds (S1 Table), among them sulfur-containing volatiles such as methanethiole, dimethyl disulfide ( 1 ), dimethyl trisulfide ( 2 ), S -methyl ethanethioate ( 3 ), S -methyl propanethioate ( 4 ), S -methyl 2-methylpropanethioate ( 5 ), S -methyl 3-methylbutanethioate ( 6 ) and S -methyl phenylethanethioate ( 7 ), as well as γ-decalactone ( 8 ) (S3 Fig). Some these compounds, for example, dimethyl trisulfide and S -methyl 3-methylbutanethioate, have been associated with inhibition of a variety of plant pathogens [52,53], suggesting they may play a role in suppression of amphibian fungal pathogens, such as Bd and Bsal .…”
Section: Resultsmentioning
confidence: 99%